Assessment of the dynamics of x-ray morphometric indices of the jaws in children with variable bite - Макєєв, Валентин Федорович; Ісакова, Ольга Олексіївна (Actual Dentistry, 2021)
Purpose: to determine the peculiarities of the dynamics of the roentgenomorphometric indices of the jaws in children during the period of mixed bite. Materials and methods. The study assessed the dynamics of radiological indices (mental index (MI), gonial index (GI), upper and lower panoramic mandibular indices (PMI-S and PMI-i)). The study used orthopantomograms of 107 children (65 boys and 42 girls) aged 6–13 years from Lvov and Lviv region. All children were divided into age groups with the preservation of a proportional and harmonious distribution, both by sex and by age. Results. After evaluating the results of the study, the age periods of active restructuring of the bone structure of the child’s jaws were identified. A characteristic feature of variations in index indicators is different age phases of active changes for boys and girls. The only common period for both sexes is the age of 9–10 years, when there is an increase in almost all index indicators, which coincides with the beginning of the eruption of multi-rooted teeth. Conclusions. Evaluation of index indicators using orthopantomograms in children during the period of mixed bite is an important diagnostic criterion for detecting active morphometric changes in the bone structures of the maxillofacial region, as well as an auxiliary diagnostic criterion when planning the timing of dental or orthodontic intervention. Key words: orthopantomogram, radiological indices, mental index, gonial index, upper and lower panoramic mandibular indices.